2011
DOI: 10.1111/j.1365-2966.2011.19143.x
|View full text |Cite
|
Sign up to set email alerts
|

Early magnetic B-type stars: X-ray emission and wind properties

Abstract: We present a comprehensive study of X-ray emission and wind properties of massive magnetic early B-type stars. Dedicated XMM-Newton observations were obtained for three stars xi1 CMa, V2052 Oph, and zeta Cas. We report the first detection of X-ray emission from V2052 Oph and zeta Cas. The observations show that the X-ray spectra of our program stars are quite soft. We compile the complete sample of early B-type stars with detected magnetic fields to date and existing X-ray measurements, in order to study wheth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 105 publications
(210 reference statements)
11
144
0
Order By: Relevance
“…Following the formalism of Petit et al (2013), with the stellar parameters listed in Table 2, a rotation period of 1.2 days, and a lower limit on the dipolar magnetic field of 1.5 kG, we derived a Keplerian co-rotation radius of 2.1 stellar radii and a lower limit on the Alfvén radius of 17.6 stellar radii. For these calculations, we further adopted a mass-loss rate of 1.4×10 −10 M yr −1 (Krtička 2014) and a terminal velocity of 700km s −1 (Prinja 1989;Oskinova et al 2011). Following the results of Petit et al (2013), ρ Oph A should host a centrifugal magnetosphere, and the interplay between the stellar magnetic field and rotation rate may be able to sustain a circumstellar disk.…”
Section: Observations Data Reduction and Resultsmentioning
confidence: 99%
“…Following the formalism of Petit et al (2013), with the stellar parameters listed in Table 2, a rotation period of 1.2 days, and a lower limit on the dipolar magnetic field of 1.5 kG, we derived a Keplerian co-rotation radius of 2.1 stellar radii and a lower limit on the Alfvén radius of 17.6 stellar radii. For these calculations, we further adopted a mass-loss rate of 1.4×10 −10 M yr −1 (Krtička 2014) and a terminal velocity of 700km s −1 (Prinja 1989;Oskinova et al 2011). Following the results of Petit et al (2013), ρ Oph A should host a centrifugal magnetosphere, and the interplay between the stellar magnetic field and rotation rate may be able to sustain a circumstellar disk.…”
Section: Observations Data Reduction and Resultsmentioning
confidence: 99%
“…Our analysis of the X-ray spectra of HR 5907 and HR 7355 shows that these stars are even harder X-ray sources than σ Ori E; the emission-measure-weighted temperature of the hot plasma in HR 5907 is 80 MK and that in HR 7355 is 60 MK, for instance. Given that the winds in magnetic B-type dwarf stars are weak, with velocities not exceeding a few hundred km s −1 (Oskinova et al 2011b), it is very difficult to explain such high temperatures in the framework of the magnetically confined wind shock model (Babel & Montmerle 1997). On the other hand, non-thermal emission can be expected from stars with strong magnetic fields (Leto et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Initial 1D hydrodynamic simulations showed that clumps merge and grow in size while moving away from the stellar surface, leading to large variations in the local density (up to 4 orders of magnitude) and velocity (a factor of few). In these simulations, collisions between clumps were also shown to be able to produce a remarkable amount of X-rays (Feldmeier, 1995;Feldmeier et al, 1997;Cohen et al, 2010;Oskinova et al, 2011Oskinova et al, , 2012Leutenegger et al, 2013). 2D hydrodynamical simulations later questioned the formation of large clumps, as in the multi-dimensional approach these structures are disrupted by the thin-shell and Rayleigh-Taylor instabilities (Dessart and Owocki, 2002.…”
Section: Take the Rough With The Smoothmentioning
confidence: 98%